Ants reign over a distinct microbiome in forest soil. (December 2019) - Lindström, Stafva; Timonen, Sari; Sundström, Liselotte; Johansson, Helena
Abstract: Biotic and abiotic characteristics shape the microbial communities in the soil environment. Manipulation of soil, performed by ants when constructing their nests, radically changes the soil characteristics and creates a unique environment, which differs in its composition, frequency and abundance of microbial taxa, from those in the reference soils. We sampled nests of the mound-building ant Formica exsecta, and the surrounding reference soils over a three-month period, and generated NGS (Illumina MiSeq), and T-RFLP data of the bacterial and fungal communities. We used ordination techniques and network analysis to disclose the community structure, and we assessed the variation in diversity, evenness and enrichment of taxa between the two environments. We also used indicator analysis to identify the potential core microbiome of the nests. Our results show that the bacterial and fungal communities, in the rigorously curated nest environment, are significantly different from those in the reference soils, in terms of community structure and enrichment of characteristic indicator taxa. We demonstrate that the nests represent a niche, where microbial species can adapt and diverge from the communities in the surrounding soils. Our findings contribute to our understanding of the composition and function of microbiomes in fragmented habitats. Highlights: Microbes in F. exsecta nests are unique, compared to the ones in reference soils. Microbial community structure differs significantly between the two environments. The core microbiome of the nests contains potential ant symbiotic Actinobacteria.